Governance, institutions, and regional infrastructure in Asia - Prabir De (Asian Development Bank Institute (ADBI), 2010)
This study is a comprehensive, empirical analysis of the linkages between governance, institutions, and regional infrastructure. The empirical results indicate that governance and institutions are crucial for regional infrastructure development: every one point improvement in governance results in a 1 to 1.5 point rise in regional infrastructure. Countries (and regions) with higher income, stronger institutions, better governance, and more open economies are likely to have higher levels of regional infrastructure. The findings of this paper suggest that our efforts to promote regional infrastructure must not be limited to traditional policy measures aimed at attracting investment in infrastructure, but must also address policy reform across a number of areas. Thus, institutions and governance must play an important complementary role in strengthening Asia's regional infrastructure.
Keywords: O19; F10; F15; 330; Infrastruktur; Institutionelle Infrastruktur; Governance-Ansatz; Asien